Polymorphic microsatellite DNA markers for Banksia attenuata (Proteaceae) - He, Tianhua; Krauss, S.; Lamont, Byron (Blackwell, 2007)
We developed 11 polymorphic microsatellite DNA markers for an Australian native shrub Banksia attenuata. The number of alleles per locus in 50 individuals varied from five to 18, observed and expected heterozygosities ranged from 0.300 to 0.740 and from 0.537 to 0.918, respectively. Six loci showed no significant deviation from Hardy Weinberg equilibrium (P > 0.05), and null alleles appear to exist at locus BA-B1. All loci showed independent inheritance.